Valorization of mangoes with internal breakdown through the production of edible films by continuous solution casting. (June 2021) - Oldoni, Fernanda C.A.; Bernardo, Marcela P.; Oliveira Filho, Josemar G.; de Aguiar, Aline C.; Moreira, Francys K.V.; Mattoso, Luiz H.C.; Colnago, Luiz A.; Ferreira, Marcos D.
Abstract: Mangoes are usually wasted by consumers due to a physiological disorder known as Internal breakdown (IB). In this study, Palmer mangoes affected by IB were valorized by turning into edible films by continuous solution casting. The films were produced using mango pulps with different IB levels, being 0 (no IB), 2 (1/3–2/3 of IB-affected pulp) and 3 (more than 2/3 of IB-affected pulp), and pectin as a matrix former. The influence of IB level on the physicochemical composition of mango pulps was assessed by pH, soluble solid content, and fiber content analyses. Continuous casting allowed for high productivity of edible films with natural mango color attributes. The films obtained from mango pulps with the highest IB level displayed lowest thickness and water vapor permeability, and largest elongation and opacity, in addition to exhibiting a short composting time (10 days). The physical properties of mango edible films are influenced by the pulp physiochemical composition which changes with IB progression. Highlights: Mangoes with internal breakdown were turned into edible films by continuous casting. The natural mango pulp color was retained in films after fast processing at 100 °C. Internal breakdown level/edible film property correlations were described. Collapsed mango pulp-based films are potential candidates for edible packaging.